Effect of Giving Plantains and Ambon Bananas on Muscle Endurance in SSB ESGE Tuban Adolescent Athletes - Sari, Lia Novita; Munir, Miftahul (Universitas Negeri Medan, 2024)
Physical fitness is the body's ability to adjust to physical loads so that it can avoid excessive fatigue. Higher physical fitness can reduce the possibility of muscle fatigue. This study aims to determine the endurance of athletes. The type of research is